PDIP vs Gerindra: Political Marketing Communication Through Instagram Ahead of the 2024 Election - Muhammad Rio Fariza; Pawito; Andre Novie Rahmanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article reviews the role of social media Instagram in the political marketing communications of the PDI Perjuangan and Gerindra Party ahead of the 2024 Election; the election of these two parties is the subject of study because they are the political parties that won the 2019 Election with votes and won the most number of seats. Research using qualitative methods. Data were analyzed using qualitative content analysis by observing the Instagram accounts @pdiperjuangan and @gerindra. The study results show that Instagram is operated by political parties in digital marketing communications to attract public sympathy. The form of political marketing communication that is spread has a variety of themes and types of uploaded content